2015
DOI: 10.3109/21678421.2015.1026826
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center screening trial of rasagiline in patients with amyotrophic lateral sclerosis: Possible mitochondrial biomarker target engagement

Abstract: OBJECTIVE Rasagiline, a monoamine oxidase B inhibitor, slowed disease progression in the SOD1 mouse, and in a case series of patients with amyotrophic lateral sclerosis (ALS). Here we determine whether rasagiline is safe and effective in ALS compared to historical placebo controls, and whether it alters mitochondrial biomarkers. METHODS We performed a prospective open-label, multicenter screening trial of 36 ALS patients treated with 2mg oral rasagiline daily for 12 months. Outcomes included the slope of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Blood represents an easily procurable tissue, although drug-mediated changes in blood-derived mitochondria does not ensure similar (or indeed any) changes in brain mitochondria have occurred. We recently reported a study in which lymphocyte mitochondria membrane potential values served as a biomarker of mitochondrial target engagement in amyotrophic lateral sclerosis patients treated with rasagiline [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Blood represents an easily procurable tissue, although drug-mediated changes in blood-derived mitochondria does not ensure similar (or indeed any) changes in brain mitochondria have occurred. We recently reported a study in which lymphocyte mitochondria membrane potential values served as a biomarker of mitochondrial target engagement in amyotrophic lateral sclerosis patients treated with rasagiline [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, measured by an Oxygen Radical Absorbance Capacity (ORAC) assay, was reduced. However, this study failed to find changes in the ALSFRS-R score [321]. Several larger clinical trials are in progress, which include functional and biomarker outcome measurements (clinicaltrials.gov IDs NCT01879241, NCT01786603).…”
Section: Mitochondrial Medicine In Alsmentioning
confidence: 99%
“…Thus measuring particular biomarkers related to mitochondrial function (e.g. changes in mitochondrial membrane potential, oxidative stress, and the relative abundance of pro-survival/proapoptotic signals) may allow for a biochemically-relevant measure of therapeutic effectiveness in ALS clinical trials (90). The trial did not demonstrate an improvement in the functional ALSFRS-R scores after 12 months compared to historical controls (when corrected for symptom duration).…”
Section: Clinically-relevant Biomarkers: Assessing Disease Progressiomentioning
confidence: 99%
“…A recently conducted clinical trial of rasagiline, an inhibitor of monoamine oxidase B, demonstrates the application of potential blood biomarkers in assessing the clinical outcome of a therapeutic agent (90). Prior work had demonstrated that the drug had specific beneficial effects on mitochondrial function, decreased oxidative damage, and inhibited apoptosis.…”
Section: Clinically-relevant Biomarkers: Assessing Disease Progressiomentioning
confidence: 99%
See 1 more Smart Citation